Biomechanical and physiological implications to running after cycling and strategies to improve cycling to running transition: A systematic review - Bini, R. R.; Tiago, C. J.; Jayden, H.; Figueiredo, P. (Journal of Science and Medicine in Sport, 2022)
Objectives: This systematic review summarises biomechanical, physiological and performance factors affecting running after cycling and explores potential effective strategies to improve performance during running after cycling. Design: Systematic review. Methods: The literature search included all documents available until 14th December 2021 from Medline, CINAHL, SportDiscus, and Scopus. Studies were screened against the Appraisal tool for Cross-sectional Studies to assess methodological quality and risk of bias. After screening the initial 7495 articles identified, fulltext screening was performed on 65 studies, with 39 of these included in the systematic review. Results: The majority of studies observed detrimental effects, in terms of performance, when running after cycling compared to a control run. Unclear implications were identified from a biomechanical and physiological perspective with studies presenting conflicting evidence due to varied experimental designs. Changes in cycling intensity and cadence have been tested but conflicting evidence was observed in terms of biomechanical, physiological and performance outcomes. Conclusions: Because methods to simulate cycle to run transition varied between studies, findings were conflicting as to whether running after cycling differed compared to a form of control run. Although most studies presented were rated high to very high quality, it is not possible to state that prior cycling does affect subsequent running, from a physiological point of view, with unclear responses in terms of biomechanical outcomes. In terms of strategies to improve running after cycling, it is unclear if manipulating pedalling cadence or intensity affects subsequent running performance.